Legal Analysis Of Franchise Agreements In The Culinary Sector Based On The Regulation Of The Minister Of Trade In Indonesia - Dianto, Rakhmad Wiwit; Handayati, Nur; Borman, M. Syahrul (PT. Anagata Sembagi Education, 2025)
This study analyzes the legal aspects of franchise agreements in the culinary sector based on the Regulation of the Minister of Trade No. 71 of 2019. Franchising as a rapidly growing business model in Indonesia presents legal challenges related to contract transparency, legal certainty, and the balance of rights and obligations between franchisors and franchisees. This study uses a normative legal approach by analyzing laws and regulations, legal doctrines, and franchise business practices in Indonesia. The results of the study show that although the regulation has provided a clear legal framework, its implementation still faces obstacles, especially in the aspect of supervision and understanding of business actors regarding their rights and obligations. The franchisor has protection over intellectual property rights and operational control, while the franchisee is guaranteed through the franchisor's obligation to provide technical support and training. However, weak supervision and lack of legal education for franchisees still cause unfair practices in franchise agreements. Dispute resolution through arbitration is preferable to litigation because it is faster and more flexible, but cost constraints and procedural understanding are still major obstacles. Therefore, it is necessary to strengthen regulations, increase supervision, and legal education for business actors so that franchise agreements can run more transparently, fairly, and provide legal certainty for all parties involved..